Mekanisme Eksekusi Sita Jaminan Aset Kripto di Indonesia - Chiquita Andina Putri; Yati Nurhayati; Iwan Riswandie (Jurnal Penegakan Hukum Indonesia, 2022)
Cryptocurrency is a type of virtual currency that works similarly to real money and enables users to virtually send payments for transactions involving business. With the development of crypto assets today, several pawn and loan institutions accept crypto assets as collateral objects. In the case of pawning, default can also occur which requires that the collateral from the debtor be confiscated in the event of default. The purpose of this study is to determine the legal strength of crypto assets used as collateral objects and to find out the execution mechanism for crypto asset confiscation in Indonesia in the event of default. This study used a normative juridical research method for its research. The type of information used in this study is secondary information, specifically information found through library research. The result of this research is that crypto assets can be used as collateral objects, but not as main collateral. Crypto assets as collateral objects already have strong legal force, this is based on Book II of the Civil Code, Law no. 10 of 2011 concerning Amendments to Law Number 32 of 1997 concerning Commodity Futures Trading, Regulation of the Commodity Futures Trading Supervisory Agency Number 5 of 2019 concerning Technical Provisions for the Implementation of the Physical Crypto Asset Market on the Futures Exchange. In terms of regulating the confiscation of crypto assets, it can be said that currently in Indonesia itself there are no special regulations and special institutions that regulate the confiscation of crypto assets. But the process of confiscation of crypto assets can be carried out with procedures such as foreclosure of other material guarantees.